Case Report: Keratoacanthoma and type I diabetes secondary to treatment with PM8001, a bifunctional fusion protein targeting TGF-β and PD-L1 - Qi, Rongbin; Xu, Hailing; Fu, Xinyu; Yu, Yingying; Lv, Dongqing; Li, Yujing; He, Susu (Frontiers in Oncology, 2023)
Immune-related adverse reactions primarily involve the skin and the endocrine, digestive, and respiratory systems. In the endocrine system, these adverse effects mainly include hypophysitis, thyroiditis, hypoadrenalism, and rarely, diabetes mellitus. The most common symptoms in the skin are pruritus, rash, and infrequently, eruptive keratoacanthoma. Here, we report a case of a 67-year-old woman who developed eruptive keratoacanthoma of the skin 6 weeks after beginning treatment with a bispecific antibody (PM8001), targeting both programmed cell death receptor 1 and transforming growth factor β, as well as type I diabetes mellitus–induced ketoacidosis after 13 weeks. The type I diabetes appeared to stabilize after insulin treatment, and the keratoacanthoma gradually resolved after drug discontinuation. This case report describes a case of the effects of PM8001 immunotherapy on the endocrine glands and skin, together with a review of the relevant literature, and summarizes the different clinical characteristics of rare immune-related adverse events resulting from PM8001 immunotherapy to provide a reference for their early detection, diagnosis, and treatment.